PROBLEM-BASED LEARNING (PBL) WITH QUIZIZZ: IMPROVING STUDENT LEARNING OUTCOMES IN OPTICAL INSTRUMENTS - Husna, Ikhwan Ananda; Syafrizal, Syafrizal; Halimatussakdiah, Halimatussakdiah; Muliani, Muliani; Setiawan, Tulus (JURNAL EDUSCIENCE, 2024)
This type of research is a quantitative approach with a quasi-experimental design in the form of a nonequivalent Control Group Design. The sampling technique was purposive sampling with a sample size of 50 students, namely 25 students from class XI-MIA1 as the control class and 25 students from class XI-MIA2 as the experimental class. The data collection instrument uses multiple choice questions. Meanwhile, data analysis uses prerequisite tests which include normality and homogeneity tests, hypothesis tests and N-gain tests.The results showed that the average posttest score for the experiment was 82.20 and the average posttest score for the control class was 76.20. Based on the results of hypothesis testing using parametric tests, namely the independent t-test, sig results were obtained. (2-tailed) of 0.026 < 0.05, meaning that H0 is rejected and Ha is accepted or there is an influence of the Problem Based Learning (PBL) model assisted by the Quizizz application on student learning outcomes. Meanwhile, the average N-Gain score for the experimental class is 0.72, which is in the high category. So it can be concluded that there has been an increase in student learning outcomes in the experimental class which implemented the Problem Based Learning (PBL) model assisted by the Quizzizz application.